Socioproductive and economic characteristics of criollo chili producers from Teticic, Olinalá, Guerrero - Sabino-López, Juan Elias; Guzmán-Olea, Ismaela; Antúnez-Ocampo, Óscar Martín; Vázquez-Villamar, Mirna; Rojas-García, Adelaido Rafael; Espinosa-Rodríguez, Mariana (Ecosistemas y Recursos Agropecuarios, 2025)
The chilli is a crop of cultural, economic and social importance for Mexico, it is produced and consumed throughout the national territory. The objective of analyzing the socio-productive and economic characteristics of criollo chilli producers in the community of Teticic, Olinalá, Guerrero, México, in 2021, an interview with social, economic and productive variables was applied to 39 chilli producers in the community, the information was concentrated in Excel and a hierarchical cluster analysis was carried out in the statistical program SPSS version 21 where a factor analysis was applied for the selection of variables, the Ward method and the Euclidean distance were used, which allowed to obtain five groups of producers. Chilli cultivation is a subsistence agricultural system presided over mainly by men with an average age of 47 years with basic education, dedicated mainly to agriculture with an average of 21 years of experience, using family labor. This crop faces a series of productive, commercial, post-harvest, service and support problems from the government that limit its productivity and could put at risk the conservation of chilli crioles seeds.
Keywords: Chilli; Guerrero; producers; social; economy